Development of a Software Module for Synthetic Optical Diagnostics of Plasmas in the T-15MD Tokamak and Calculation of Passive Spectroscopy Signals - Neverov, V. S.; Andreenko, E. N.; Akhtyrskiy, S. V.; Zemtsov, I. A.; Krupin, V. A.; Kukushkin, A. B.; Kukushkin, A. S.; Leonov, V. M.; Nemets, A. R.; Nurgaliev, M. R.; Pshenov, A. A. (Physics of atomic nuclei, 2023)
The development of synthetic diagnostics for passive plasma spectroscopy systems of the T-15MD tokamak is started using the Cherab software library for modeling fusion plasma spectroscopy. The calculation of signals in the visible wavelength range is performed with the Raysect code using the ray tracing technique, taking into account the reflection of light from the surfaces of the first wall specified as a full CAD model. The results of measuring the characteristics of light reflection by samples of the T-15MD graphite first wall before and after plasma exposure are used. The parameters of the model functions of graphite reflectivity are chosen by fitting the measurements. The results of edge plasma modeling by the SOLPS code are used to calculate the intensity of the spectral line H α and the fraction of reflected light in the observed intensity depending on the geometry of the line of sight. It is shown that, during radial observation of the scrape-off layer plasma, the reflected light fraction in the observed intensity does not exceed 50%, and after a long-term exposure of the wall to the plasma, it should decrease to 10–20%. For lines of sight of diagnostics that measure the effective plasma charge profile, the bremsstrahlung and photorecombination radiation spectra are calculated on the basis of the combined data of modeling by the ASTRA and SOLPS codes. It is shown that only the lines of sight observing the peripheral plasma are subject to a significant influence of reflected light, where the intensity of bremsstrahlung is minimal. As in the case of H α radiation, a long-term exposure of the wall to the plasma is expected to reduce the reflected light fraction in the observed intensity by a factor of 3–4.